Collaborative use of mobile devices to curate sources of inspiration - Lucero, Andrés; Porcheron, Martin; Fischer, Joel E. (2016)
We demonstrate a prototype mobile application designed to support individually collecting personal sources of inspiration on mobile phones, and then the sharing and curating of these collected materials in a face-to-face situation.